Tailoring MOF-5 Photocatalysts: Low-Temperature Synthesis and Solvent Variations for Enhanced Performance in Dye Degradation - Gupta, Himanshi; Saini, Isha; Singh, Vinamrita; Kumar, Tanuj; Singh, Varsha (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Metal-organic frameworks (MOFs) are emerging as pivotal porous crystalline materials with diverse applications. Typically, MOFs are synthesized using solvothermal techniques at high temperatures and pressures. In this study, a novel approach was employed to synthesize zinc-based MOFs, specifically MOF-5, at low temperatures (up to 50 °C) via chemical mixing at standard pressures. Varying the temperature and solvents, N-methyl-2-pyrrolidone (NMP) and N,N-dimethylformamide (DMF), in the chemical mixing process, the highest yield of the material was observed with DMF at 50 °C (M1). Two additional samples, M2 and M3, are synthesized at room temperature using DMF and NMP, respectively. Despite similarities in XRD, Raman, and FTIR analyses confirming successful MOF-5 formation, noticeable differences in sample morphology arise due to distinct synthesis conditions, particularly solvent and temperature variations. The MOF-5 samples exhibit UV absorption with varying band gaps. Notably, when employed as photocatalysts for organic dye (methylene blue) degradation, M2 outperforms others, achieving an impressive 85% degradation under simulated solar light irradiation. This work underscores the significance of tuning MOF photocatalyst properties through tailored synthesis routes, recognizing the profound impact of morphology and elemental composition on enhancing photocatalytic dye degradation performance. Copyright © 2024 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).